Sex Work Politics : From Protest to Service Provision - Majic, Samantha (Book collections on Project MUSE., 2014)
Samantha Majic investigates the way two San Francisco-based nonprofit organizations negotiate their governmental obligations while maintaining their commitment to outreach and advocacy for sex workers' rights as well as broader socio-political change.